Analysis of the Relationship Between Digital Reputation Index and Financial Performance of Indonesian Insurance Companies - Titiek Irewati (Journal of Social Research, 2026)
The enthusiasm of the Indonesian people for social media makes digital marketing strategies an important factor to increase brand strength through improving the company's postitf image. Social media is a place for companies to form positive online perceptions and reputations. This condition is the basis for research to find out how the consistency of positive reputation is on the financial performance of insurance companies in Indonesia. The relationship between the Digital Reputation Index (IRD) on the financial performance of insurance companies (gross premiums, productivity ratio and company profit) was analyzed based on data from 12 life insurance companies and 12 conventional general insurance companies respectively. The Spearman correlation test resulted in a significant positive directional relationship for the Digital Reputation Index to gross premiums (for life and general insurance companies). A non-significant positive directional relationship between the Digital Reputation Index and the Productivity Ratio (life and general insurance). A non-significant positive directional relationship between the Digital Reputation Index and the profits of life insurance companies while a significant positive relationship occurs with the profits of general insurance companies.